LA RELACIÓN ENTRE EL VALOR DE LA MARCA, PERCEPCIÓN DE MARCA E IMÁGENES AFECTIVAS IAPS (INTERNATIONAL AFFECTIVE PICTURE SYSTEM) - Fischer, Laura; Chávez, David; Zamora, Oscar (European Scientific Journal, ESJ, 2014)
The market today is invaded by a lot of products, line extensions anda variety of brands that compete for positioning, recall and be first whenmaking a purchase decision. The processes of persuasion are made throughthe conceptual values of the brand in combining proper sharp image, in thisexperimental study whose primary objective was to determine if the value ofthe brand affects the perception of affective image, participated 423 StudentsUniversity in Mexico City from 19 to 25 years. Ninety photographs of theIAPS (International Affective Picture System) model bioinformational Lang(1994) highly emotional, with 30 positive feedbacks (6-9 points) and 30negative (1-3 points) were used. Emotional and 30 neutral images (4-5points). Subsequently 30 brands positioned in the Mexican market, selectedfrom the list of BrandZ, Millward Brown Top 100 (2012) were taken. Eachof these brands was inserted into a positive image, in a neutral and negative.The images were assessed using a Likert scale nine intervals, the pictures,recording responses, were performed through SuperLab version 4.5 program.The results suggest that the value of a brand can alter the perception of theimage presented, allowing a proposed analysis in the field of marketing todevelop strategies for graphic communication.